Chemogenetic Tools and their Use in Studies of Neuropsychiatric Disorders - Neřoldová, M; Stuchlík, A (Physiological research, 2024)
Chemogenetics is a newly developed set of tools that allow for selective manipulation of cell activity. They consist of a receptor mutated irresponsive to endogenous ligands and a synthetic ligand that does not interact with the wild-type receptors. Many different types of these receptors and their respective ligands for inhibiting or excitating neuronal subpopulations were designed in the past few decades. It has been mainly the G-protein coupled receptors (GPCRs) selectively responding to clozapine-N-oxide (CNO), namely Designer Receptors Exclusively Activated by Designer Drugs (DREADDs), that have been employed in research. Chemogenetics offers great possibilities since the activity of the receptors is reversible, inducible on demand by the ligand, and non-invasive. Also, specific groups or types of neurons can be selectively manipulated thanks to the delivery by viral vectors. The effect of the chemogenetic receptors on neurons lasts longer, and even chronic activation can be achieved. That can be useful for behavioral testing. The great advantage of chemogenetic tools is especially apparent in research on brain diseases since they can manipulate whole neuronal circuits and connections between different brain areas. Many psychiatric or other brain diseases revolve around the dysfunction of specific brain networks. Therefore, chemogenetics presents a powerful tool for investigating the underlying mechanisms causing the disease and revealing the link between the circuit dysfunction and the behavioral or cognitive symptoms observed in patients. It could also contribute to the development of more effective treatments.
Keywords: Neurons; Designer Drugs; Mental Disorders; receptory spřažené s G-proteiny; duševní poruchy; zvířata; Humans; nové syntetické drogy; Clozapine; klozapin; neurony; lidé; Receptors, G-Protein-Coupled; Animals